Design of Faster SMS4 Crypto System with Efficient XOR Gate - Babu M., G. A. Sathish Kumar (International Journal of Advanced Science and Technology, 2020)
In this internet era, the security of data over a wireless medium is the biggest challenge. And the faster processing and transmission of data also a big challenge in areas like defense and medical field. In this paper, the design of faster SMS4 cryptosystem is carried out with the efficient XOR gate designs. From the implementation results obtained using Kintex 7 FPGA, it is proved that the Pipelined SMS4 cryptosystem with 4 transistor XOR gate design based on GDI logic is faster than other SMS4 cryptosystems with a delay of only 1.37ns.